International Accreditation Preparation Model in Accredited Prodi A at Universitas Muhammadiyah Sumatera Utara - Dedi Amrizal; Isnina Isnina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to: 1) find out data and information related to the readiness of study programs that have been accredited A at the Muhammadiyah University of North Sumatra in order to participate in international accreditation; 2) to find out how to create and determine the readiness model of study programs that have been accredited A in following international accreditation at the Muhammadiyah University of North Sumatra; 3) to implement and improve the international accreditation preparation model for study programs that have been accredited A at the Muhammadiyah University of North Sumatra. The research method used is research and development using Borg and Gall. Borg and Gall applied only up to step 5 only. This is because the ultimate goal of this research is to apply the model that has been found. The 5 steps start from initial research, determining the model, implementing the model and improving the model. To find the condition and readiness of the study program used descriptive research methods with categorization analysis for the measuring instrument. The results of this study were analyzed to determine the model for implementing the study program's readiness to carry out international accreditation. The model formed will be applied to one study program. The results of this application will be used to improve the first model that has been formed and applied earlier. Through this research, a model for implementing international accreditation has been found for study programs that have been accredited A by BAN PT at UMSU. This model can be used as material for other study programs in carrying out international accreditation and can be imitated by study programs at other universities with the same desire. The output of this research is being worked on because the research process has just been completed.